Upaya Meningkatkan Teknik Dasar Pukulan Forehand Smash pada Permainan Tenis Meja melalui Latihan Shadow - Mahfuz; Hariadi; Tiawan, Riskika Agus; Arkanuddin, Zaenul (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study was to determine the effect of shadow training on improving the basic technique of forehand smash in table tennis for tenth grade students of SMK NWDI Pancor. The forehand smash technique is an important component in table tennis that requires good movement coordination, proper body position, and accurate arm swing. However, initial observations showed that many students had difficulty in mastering this technique optimally. A quantitative approach was applied in this study, using a pre-experimental design as its main framework, a one-group pretest-posttest design. The research sample consisted of 25 students selected through a saturated sampling technique. The data collection instrument was a practical test with assessment aspects including body position, arm swing, shot accuracy, and coordination. The results of data analysis showed an increase in the average score from 46.6 in the pretest to 64.6 in the posttest. Hypothesis testing using the paired sample t-test method produced a significance value of 0.000 (p < 0.05), indicating that shadow training had a significant impact on improving the basic technique of forehand smash. Thus, shadow training has been proven effective in improving students' basic table tennis skills, especially in terms of forehand smash, and is recommended as an alternative learning method in physical education.